Innovation and de facto standardization: The influence of dominant design on innovative performance, radical innovation, and process innovation. (April 2016) - Brem, Alexander; Nylund, Petra A.; Schuster, Gerd
Abstract: Setting technology standards is the route to market growth and to potentially influencing the performance of a whole industry. When a market accepts a particular technology as one that defines the specifications for products in the entire industry, a dominant design is set. In this article, we investigate how the existence of a dominant design affects subsequent innovation in an industry. In particular, we study the influence on innovative performance, radical innovation, and process innovation. Analyzing longitudinal, cross-sectional patent data for more than 2.6 million patents filed from 1978 to 2013, we find support for our hypotheses that an industry's innovative performance and degree of radical innovation are negatively influenced by dominant design in that industry, and that process innovation is fostered by the occurrence of a dominant design. We discuss the findings in the light of the increasing speed of technological development and standardization. Additionally, results from a sensitivity analysis for different threshold values of dominant design call for adjusting a binary definition of dominant design with different threshold values depending on the effects under study. Highlights: This paper investigates on how the existence of a dominant design affects innovative performance, radical innovation and process innovation. We analyse longitudinal and cross-sectional patent data for more than 2.5 million patents filed from 1978 to 2013. Our results indicate that an industry's innovative performance and degree of radical innovation are negatively influenced by dominant design in that industry. We show that process innovation is fostered by the occurrence of a dominant design.